2014
DOI: 10.18632/oncotarget.2887
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic regulation of monocyte chemotactic protein 1 leads to enhanced macrophage recruitment and ovarian carcinoma growth

Abstract: Increased adrenergic signaling facilitates tumor progression, but the underlying mechanisms remain poorly understood. We examined factors responsible for stress-mediated effects on monocyte/macrophage recruitment into the tumor microenvironment, and the resultant effects on tumor growth. In vitro, MCP1 was significantly increased after catecholamine exposure, which was mediated by cAMP and PKA. Tumor samples from mice subjected to daily restraint stress had elevated MCP1 gene and protein levels, increased CD14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 19 publications
2
60
0
Order By: Relevance
“…Patients with endometrial cancer have significantly higher monocyte counts in pretreatment blood samples compared to healthy non-cancer controls [26]. In other types of gynecologic malignancy, an elevated circulating monocyte count was associated with decreased survival in both ovarian and cervical cancers [27,28]. However, to date, no study has reported the impact of monocyte counts on endometrial cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with endometrial cancer have significantly higher monocyte counts in pretreatment blood samples compared to healthy non-cancer controls [26]. In other types of gynecologic malignancy, an elevated circulating monocyte count was associated with decreased survival in both ovarian and cervical cancers [27,28]. However, to date, no study has reported the impact of monocyte counts on endometrial cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenergic stimulation of inflammatory arachidonic acid metabolism can also promote tumour growth 71 . Several in vivo studies have shown that SNS stimulation of inflammatory signaling can enhance tumour progression and metastasis 49,72 . However, no studies have yet determined whether SNS effects on inflammation are sufficient to increase rates of tumour initiation.…”
Section: Sns Regulation Of Cancer Biologymentioning
confidence: 99%
“…β-adrenergic signaling can markedly enhance macrophage recruitment into the tumour parenchyma by stimulating tumour cells’ production of chemotactic factors such as macrophage colony stimulating factor (CSF1, also known as M-CSF) and MCP-1 49,72 . β-adrenergic signaling may also enhance the density of tumour-associated macrophages by stimulating myelopoietic development of precursor monocytes in the bone marrow 7,27 and spleen 26 , which can then be recruited into the tumour microenvironment (Figure 1).…”
Section: Sns Regulation Of Cancer Biologymentioning
confidence: 99%
“…Adrenergic regulation of MCP1 also plays a key role in TAM recruitment. The local stress reaction and systemic stress state all may contribute to the overexpression of MCP1 gene and lead to tumor progression [66,67,69] Melanoma TGF-b induces vascular endothelial growth factor-C expression in melanoma TAM and promotes melanoma lymph node metastasis. There is a positive correlation of M2 and survival and proliferation of melanoma cell [72] Cervical cancer CSF1 inhibition delays cervical tumor growth by attenuating the turnover of TAM and enhancing infiltration by CD8 ?…”
Section: Tams and Gastric Cancermentioning
confidence: 99%
“…The local stress reaction and systemic stress may contribute to the overexpression of MCP1 gene and lead to tumor progression [67]. Homeobox gene HOXA9 is considered similar to MUC2 and MCP1 in the induction of M2 macrophages [68].…”
Section: Tams and Ovarian Cancermentioning
confidence: 99%